2020
DOI: 10.3390/plants9091119
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of a Supercritical Fluid (Sfe-CO2) Extract from Baeckea frutescens L. Leaves and Its Bioactivity Against Two Pathogenic Fungi Isolated from the Tea Plant (Camellia sinensis (L.) O. Kuntze)

Abstract: Colletotrichum gloeosporioides and Pseudopestalotiopsis camelliae-sinensis are the two most important tea plant (Camellia sinensis L.) pathogenic fungi. Interest in natural plant extracts as alternatives to synthetic chemical fungicides to control plant pathogens is growing. In this study, the volatile fraction of Baeckea frutescens L. was extracted by supercritical fluid extraction (SFE-CO2), and its chemical composition was analyzed, and investigated for its antifungal activity against C. gloeosporioides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, 1-Limonene (2.47%) and 3-Cyclohexene-1-methanol, .al (3.32%), the other constituent components are below 1%. In another study, it was found that there were 27 components that make up essential oils, including Beta-caryophyllene (28.05%), alpha-caryophyllene (24.02%), gamma-cadinene (6.29%), eucalyptol (5.46%) and Beta-pinene (5.21%), terpineol (4.54%), cubenol (2.81%) and gamma-terpinene (2.49%) [14]. The differences in the components of the essential oil of Baeckea frutescens L are caused by several factors which may be related to differences in geographical location, harvest time, local climate and plant physiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 1-Limonene (2.47%) and 3-Cyclohexene-1-methanol, .al (3.32%), the other constituent components are below 1%. In another study, it was found that there were 27 components that make up essential oils, including Beta-caryophyllene (28.05%), alpha-caryophyllene (24.02%), gamma-cadinene (6.29%), eucalyptol (5.46%) and Beta-pinene (5.21%), terpineol (4.54%), cubenol (2.81%) and gamma-terpinene (2.49%) [14]. The differences in the components of the essential oil of Baeckea frutescens L are caused by several factors which may be related to differences in geographical location, harvest time, local climate and plant physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, it was found that citronella oil from C. nardus L. has the potential as a biopesticide and insecticide [12,13]. Baeckea frutescen L contains essential oils of esters and produces essential oils of 0.071% and has potential as a fungicide and larvicide [8,11,14]. Therefore, testing the essential oil content of B. frutescen L and C. nardus L. from Bangka Belitung is necessary to obtain the right formulations in development to be used as natural insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…50 B frutescens leaf oil controlled the growth of Pseudopestalotiopsis camelliae, Colletotrichum gloeosporioides, Enterococcus faecalis, and Candida albicans, with MIC values of 5.11, 4.79, 64, and 16 µg/mL, respectively. 16,42 In another approach, the leaf oils extracted by HE and enzymatic surfactant-ultrasonic microwave extraction (ES-UME) exhibited the same antimicrobial activity against C albicans (MIC 1.25%), S aureus, E coli, and B subtilis (MIC 0.625%), Pseudomonas aeruginosa, and Propionibacterium acnes (MIC 0.3125%). 51 Besides antimicrobial activity, B frutescens leaf oil showed 24and 48-h LC 50 values of 15.31-81.72 µg/mL and LC 90 values of 34.69-116.6 µg/mL against Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus.…”
Section: Antimicrobial and Mosquito Larvicidal Activitiesmentioning
confidence: 99%
“…Currently, eucalyptol has garnered increasing interest, not only in the pharmaceutical and cosmetic industries (Cai et al 2021;Hoch et al 2023) but also in agriculture. This interest stems from its notable toxicity against various pest insects and phytopathogenic fungi (Jiang et al 2020;Tahiri et al 2022;Tripathi and Mishra 2016), coupled with its facile biodegradability and minimal impact on the environment and human health (Batish et al 2008).…”
Section: Introductionmentioning
confidence: 99%